Exploring Stock Return Discontinuities in the Japanese Banking Industry - Chikashi Tsuji (Journal of Management Research, 2024)
This study examines stock return discontinuities in the Japanese banking sector, and we derive the following interest findings. First, our statistical tests evidence that our extended econometric model incorporating a fat-tailed and skewed density and considering return discontinuities is highly effective for estimating the Japanese banking sector stock return volatilities more accurately. Second, the estimated volatilities for the Japanese banking sector stock returns from our extended model incorporating a fat-tailed and skewed density and considering return discontinuities sharply increase during the Lehman crisis and the European debt crisis and at the time of Brexit and the COVID-19 crisis.